2015
DOI: 10.5604/01.3001.0009.2114
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas Systems in Prokaryotes

Abstract: A b s t r a c tProkaryotic organisms possess numerous strategies that enable survival in hostile conditions. Among others, these conditions include the invasion of foreign nucleic acids such as bacteriophages and plasmids. The clustered regularly interspaced palindromic repeats-CRISPRassociated proteins (CRISPR-Cas) system provides the majority of bacteria and archaea with adaptive and hereditary immunity against this threat. This mechanism of immunity is based on short fragments of foreign DNA incorporated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 107 publications
(120 reference statements)
0
16
0
Order By: Relevance
“…Phage genes and CRISPR repeats were detected in all strains, and phage that were inducible by the SOS response were detected in most. Therefore, prior exposure to phage could influence strain stability in the face of an inducing stimulus or a newly introduced phage (Burmistrz & Pyrć, 2015). If this were the case, then it would be a combination of genetic composition of the strain and the environment of the bacterial population that would cause a decline in the numbers of lactobacilli.…”
Section: Discussionmentioning
confidence: 99%
“…Phage genes and CRISPR repeats were detected in all strains, and phage that were inducible by the SOS response were detected in most. Therefore, prior exposure to phage could influence strain stability in the face of an inducing stimulus or a newly introduced phage (Burmistrz & Pyrć, 2015). If this were the case, then it would be a combination of genetic composition of the strain and the environment of the bacterial population that would cause a decline in the numbers of lactobacilli.…”
Section: Discussionmentioning
confidence: 99%
“…All the F. nucleatum strains in the CRISPR database (http://crispr.i2bc.paris-saclay.fr/) 36 have one CRISPR with the number of spacers ranging from 3 to 52, (average approximately 25 spacers). Porphyromonas gingivalis , the major etiologic agent associated with chronic periodontitis, and for which no lytic bacteriophage has yet been isolated, has very extensive CRISPR immune mechanisms 39,40 . Each P. gingivalis strain in the database has more than one confirmed CRISPR locus (some with a maximum of five), with the total number of spacers in each bacterial strain ranging from 14 to 136 (http://crispr.i2bc.paris-saclay.fr/).…”
Section: Discussionmentioning
confidence: 99%
“…Stanley UPM 517 genome except for Type IV. The CRISPR-Cas system plays a significant role in the bacterial adaptive immune system (Barrangou & Marraffini, 2014; Burmistrz & Pyrć, 2015; Rath et al, 2015) and its combination with the RMS improves the bacteriophage’s resistance level (Dupuis et al, 2013). It was found that the S .…”
Section: Discussionmentioning
confidence: 99%